Wpływy bizantyńskie w średniowiecznej kulturze bułgarskiej - Gjuzelew, Wasil (Przegląd Nauk Historycznych, 2009)
Bulgaria, a neighbour of Byzantium, though related to the empire in respect of its religion, culture, and sometimes even transformed into a Byzantine province, never turned into its integral part nor copy or emulator. It cannot be doubted that it was the Church thanks to which the spirit of Byzantium most profoundly penetrated into the way the medieval Bulgarians thought and acted. From the mid. IX c. onwards, the Bulgarian Church was dominated by its Byzantine ecclesiastic counterpart, whose major centers (Constantinople, Thessaloniki and Mount Athos) exercised spiritual guidance over the subjects of Bulgarian rulers. Christianization and gradual Slavization of the Bulgarian state introduced Bulgaria into Christian and European cultural universalism. However, it should be also remembered that the same process also settled Bulgaria comfortably within the borders of the Byzantine commonwealth. These were the court of the ruler and subsequent capital centers of the Bulgarian state which were especially prone to followin the footsteps of the Byzantines and to be affected by Byzantine influences. However, medieval Bulgaria adopted the Byzantine model of government and culture only partially and remodeled it to suit its own, Le. Bulgarian, interests. Moreover, it was Bulgaria which made the Byzantine model known to Slavic orthodoxy (Serbian and Russian), the Vlachs and the Moldavians, thereby widening the spatial scope of Byzantine impact.